Key words as Language Mechanism for Creating the Text Attractiveness in Internet Discourse (on Material of Russian Universities Sites) - A. I. Pomazov (Научный диалог, 2019)
The article is devoted to the problem of using key words in the modern Russian Internet discourse in the aspect of attracting the attention of potential audience - users of educational sites. The purpose of this study is to carry out a comprehensive analysis of key words as a language means of creating attractiveness in media texts of Russian universities. The study is based on the method of statistical calculation of the occurrence of words and selection among the most frequent units of the text semantically related to the interests of the target audience of the text. The material for the study is media texts from the sites of Russian universities participating in the Program of increase of competitiveness of leading Russian universities among the world’s leading scientific and educational centers (5-100). It is shown that the set of linguistic means of expression of attractiveness category in Internet communication through the use of key words is very diverse and is constantly evolving and improving: verbs in imperative form; language units, comprising a positive evaluation ( high , best , most , international , leading , future , free , opportunity , etc.); means of dialogization and intimization of the statement (the words we , you , our , yours , etc.); onomastic attraction - playing with the names of universities. The practical significance of the study is that its results can be used to improve the work of educational institutions with the audience in the media environment.